A Review on Big Data Implementation in Agriculture - Abdul Azzam Ajhari; Albertus E.K. Gunawan; Budi Candra; Bona T. Munthe (Internasional Journal of Data Science, Engineering, and Anaylitics, 2022)
Significant population growth has been an issue lately. This means that crop production should be increased significantly to cater to the growing number of people. With less land to grow it on, changing climate and depletion of viable farmland, big data has been considered a promising approach to solve the problem. This main contribution of this study is to provide overview of the benefits of big data implementation in agriculture and the stakeholders involved by performing asystematic literature review on relevant papers. This study reveals that big data implementation brings benefits such as increase in revenue, support for sustainable agriculture, and support for data driven decision making. For successfulimplementation, stakeholders’ involvement from various sectors are needed.